State-of-the-art review on power grid resilience to extreme weather events: Definitions, frameworks, quantitative assessment methodologies, and enhancement strategies - Jufri, Fauzan Hanif; Widiputra, Victor; Jung, Jaesung (Applied Energy, 2019)
The rise of power outages caused by extreme weather events and the frequency of extreme weather events has motivated the study of grid resilience. This paper presents a state-of-the-art review of existing research on the study of grid resilience, which focuses on the point of view of power system engineering with respect to extreme weather events. Firstly, it investigates confounding terminologies used in the study of grid resilience, such as the definitions, the differences with grid reliability, the extreme weather events, and their extreme impact on the power systems. Secondly, it presents a grid resilience framework as a general provision to understand the subjects in the study of grid resilience. Thirdly, it describes several methodologies of grid resilience assessment and some quantitative indices. Finally, various grid resilience enhancement strategies implementations are discussed.
Keywords: Grid resilience; Grid resilience assessment; Grid resilience definition; Grid resilience framework; Resilience index; Grid resilience; Grid resilience assessment; Grid resilience definition; Grid resilience enhancement; Grid resilience framework; Grid resilience index